Práticas pedagógicas do professor de matemática em tempos de pandemia - SOARES, Jaila de Sousa (2022)
The research aims to analyze the pedagogical practices of Mathematics teachers during the period of remote classes and their impacts on the learning of students in the 6th year of Elementary School, due to the pandemic moment that Brazil and the world are in. The work was developed in a qualitative approach and operationalized through a questionnaire applied to Mathematics teachers in the 6th year of Elementary School, and the data analysis was anchored in the relevant bibliography. It was found that the process of remote classes mobilized teachers, students and parents, and that, although teachers sought ways to teach during this period, most students did not have access to digital information and communication technologies, which it interfered from the relationship between teachers and students and between them, to the organization of pedagogical work, resulting in difficulties in learning.